2003
DOI: 10.2307/1519759
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Disadvantage and Health: Long-Term Consequences of Obesity?

Abstract: Drawing from cumulative disadvantage theory, the health consequences of obesity are considered in light of the accumulation of risk factors over the life course. Two forms of compensation are also examined to determine if the risk due to obesity is persistent or modifiable. Analyses make use of data from a national survey to examine the consequences of obesity on disability among respondents 45 years of age or older, tracked across 20 years (N = 4,106). Results from tobit models indicate that obesity, especial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
206
1
6

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 313 publications
(223 citation statements)
references
References 86 publications
(88 reference statements)
10
206
1
6
Order By: Relevance
“…They concluded that obesity, especially early in life, is consistently related to body disability. Moreover, the results show that obesity affects the life course considerably due to the long-term consequences during adulthood (Ferraro & Kelley-Moore, 2003). These findings support the idea that the long term consequences of obesity may be considered an accumulation of risk factors over the life course.…”
supporting
confidence: 78%
“…They concluded that obesity, especially early in life, is consistently related to body disability. Moreover, the results show that obesity affects the life course considerably due to the long-term consequences during adulthood (Ferraro & Kelley-Moore, 2003). These findings support the idea that the long term consequences of obesity may be considered an accumulation of risk factors over the life course.…”
supporting
confidence: 78%
“…Because childhood is of particular import for the development of factors that help differentiate life course trajectories (O'Rand, 1996;Shaw & Krause, 2002), adverse experiences and disadvantage occurring during this time may erode psychosocial resources. Individuals who encounter adverse experiences early in life may be set on a trajectory of disadvantage that ultimately results in negative health outcomes (Ferraro & Kelley-Moore, 2003;Wickrama, Conger, Wallace, & Elder, 2003).More generally, cumulative disadvantage theory explains the differences among people that occur over time (Dannefer, 2003). It has been used to explain cohort differences in a variety of socioeconomic indicators (Ross & Wu, 1996;Schieman, 2001), and its applicability to health outcomes has also been established (Ferraro & Kelley-Moore, 2003;Wadsworth, 1997).…”
mentioning
confidence: 99%
“…Individuals who encounter adverse experiences early in life may be set on a trajectory of disadvantage that ultimately results in negative health outcomes (Ferraro & Kelley-Moore, 2003;Wickrama, Conger, Wallace, & Elder, 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The sociological literature has suggested that major social changes are unique in specific time periods. Certain cohorts may be immune to social changes, but they themselves have strong explanatory power of the health variations, especially at the societal level (Chen et al, 2010;Ferrao & Kelly-Moore, 2003). These assumptions remain at the hypothesis level before they are formally tested.…”
Section: Conclusion and Discussionmentioning
confidence: 99%